Digitalization and Social Inequality in Japanese Education - Akihito Fujiwara; Ravik Karsidi (Southeast Asian Journal on Open and Distance Learning, 2025)
This article critically analyzes the digital transformation of education in Japan through the lens of educational sociology. Using literature-based qualitative analysis, the study focuses on the GIGA School Program as a national policy intended to enhance equity through digital infrastructure. Despite universal device distribution and high-speed internet development, the study reveals significant disparities in implementation, especially concerning teacher readiness, household digital literacy, and regional differences. The findings indicate that digital education tends to reinforce social stratification through unequal access to cultural capital, which is consistent with Bourdieu's theory of symbolic violence. Moreover, the growing influence of EdTech companies has led to the marketization of learning, shifting students into passive consumers of standardized content. This phenomenon also erodes the humanistic and dialogical dimensions of education emphasized by thinkers such as Freire and Durkheim. The article concludes that technological reform must be grounded in social equity and educational philosophy to ensure just and meaningful learning. Recommendations include reforming teacher training, strengthening local educational support, and safeguarding education from commercial domination. Keywords:digital education, cultural capital, educational inequality, symbolic violence, EdTech